2012
DOI: 10.1089/biores.2012.0215
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the EarliestnefGene from Hemophiliacs and Local Controls in Korea

Abstract: Twenty hemophiliacs (HPs) were found to have human immunodeficiency virus type-1 (HIV-1) 1–2 years after exposure to Factor IX manufactured in Korea in late 1989. Plasma samples collected from donors O and P during their pre-seroconversion acute infection stage were used to manufacture clotting factors, including Factor IX, to treat these patients. To assess whether a genetic relationship exists between the viruses infecting HIV-1-positive HPs and those infecting plasma donors, we evaluated the nef sequences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(53 citation statements)
references
References 16 publications
6
47
0
Order By: Relevance
“…The patients had been primarily treated with imported clotting factors prior to the use of the domestic clotting factor. To date, four of these HPs have died . We reviewed medical records.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients had been primarily treated with imported clotting factors prior to the use of the domestic clotting factor. To date, four of these HPs have died . We reviewed medical records.…”
Section: Methodsmentioning
confidence: 99%
“…During the time of our present study, four HPs had already died . The remaining 16 HPs have been treated with HAART and Korean red ginseng (KRG).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analyses were also utilized for epidemiologic evaluation of HIV-infected Korean hemophilia patients [6869], and investigation of HIV-1-transmitted drug resistance (TDR) in Korea [6468707172]. Studies on TDR revealed that the drug resistance mutation was not common among treatment-naïve HIV-infected individuals in Korea, and there was little evidence to suggest that TDR in Korea is related to the clonal spread of drug-resistant strains.…”
Section: Phylogenetic Studies Among Korean Hiv-infected Individualsmentioning
confidence: 99%
“…Among various subtypes and CRFs in Korea, domestically infected Korean individuals are mainly infected with the Korean subclade of subtype B (KSB) at the level of the env, nef, pol, and vif genes. [1][2][3][4][5][6] KSB sequences were first detected in homosexual Korean HIV-1 patients in 1988. 1 Our previous studies show that these KSB sequences represent a subclade of the globally represented subtype B, indicating a founder effect.…”
mentioning
confidence: 99%
“…This finding is consistent with our previous studies on vif, pol, and nef genes. 1,5,6 TATA box sequences in both LTR were classified as TATAA for subtype B and almost all other subtypes, and CRFs. However, TAAAA instead of TATAA was identified in CRF01_AE, some cpx strains, and CPZ.US.85.US_Marilyn.…”
mentioning
confidence: 99%